Holistic multicriteria framework to assess flood risk in Garyllis river basin, Cyprus - Kountouri, Josefine; Panagiotou, Constantinos F.; Tsouni, Alexia; Sigourou, Stavroula; Pagana, Vasiliki; Kontoes, Charis; Hadjimitsis, Diofantos G. (My University, 2025)
The high occurrence and intensity of flood events at the European scale has urged the policymakers and water planners to invest time and funds for the design and implementation of effective flood management strategies that address major stages of disaster risk reduction, namely preparedness, response, recovery and mitigation. The optimal incorporation of these stages in the management plans is especially important in hydrographic networks that intersect urban units since these cities are highly vulnerable to flash floods. A holistic multicriteria framework is presented that estimates the spatiotemporal distribution of flood risk levels in the Garyllis River basin, which is located in the southern part of the island of Cyprus. A plethora of relevant information has been collected from multiple data sources, including satellite services, governmental portals, in-situ measurements, and historical records, at different spatiotemporal resolutions. For instance, a digital elevation model (DEM) with a 5 m spatial resolution was provided by the Department of Land and Surveys of Cyprus to model the topographical characteristics of the case site, the most recent land use/land cover map (2018) was extracted from Copernicus Land Monitoring Services, whereas daily precipitation data from nearby ground-based rainfall stations were provided by the Department of Meteorology. The collected data have been further verified and improved via field visits and discussions with relevant actors, harmonized in terms of spatial and temporal resolution and resampled into a common numerical grid to conduct two-dimensional hydraulic simulations (HEC-RAS) for estimating the evolution of flood hazard on the basis of water depths for different scenarios (i.e., three different return periods). The vulnerability levels of the study area are estimated by multiplying the weights and standardized scores of population age and population density, according to the most recent official governmental reports. In addition, the flood exposure was estimated on the basis of the land value. For each flood risk component, all factors are assigned equal weighting coefficients. Consequently, the flood risk indicator is estimated at each location by integrating the hazard, vulnerability and exposure indicators. The validity of the proposed methodology is tested by comparing the critical points that were identified during the on-site visits with the estimations of the flood risk levels. Consequently, escape routes and refuge regions were recommended for the worst-case scenario according to specific constraints. The results of this study have been discussed and approved by the national water authorities and will contribute to their ongoing efforts to further align with the EU priorities and strategies, particularly Floods Directive 2007/60/EC. Additionally, the outcomes of this study are expected to support social awareness regarding the actions that need to be taken.
Keywords: Garyllis river basin; multicriteria framework